Pembelajaran I’rab Dasar Berbasis YouTube: Studi Kasus pada Channel Arabic Podcast - Lestari, Hanna Tiara; Maspupah, Siti Imas; Kamil, Haykal Farhan (Department of Arabic Education - Faculty of Educational Sciences, 2024)
This research aims to provide a clear and comprehensive description of Arabic language learning materials focused on i’rab for beginners, using a case study of the Arabic podcast channel on YouTube. The study employs a descriptive qualitative research method through content analysis, concentrating on the i’rab material presented in the videos. The hypothesis proposed in this research suggests that YouTube can serve as an effective medium for learning Arabic, accessible to users anytime and anywhere. The researcher analyzes and presents several videos as resources or learning tools for beginners, focusing on four specific videos about i’rab. These videos are examined in terms of content, highlighting both the strengths and weaknesses of the material presented. Additionally, the research delves into the educational value and accessibility of the content, providing insights into how such platforms can enhance language learning for beginners.